GUILD PAKAN KOMUNITAS BURUNG DI DKI JAKARTA - Walid Rumblat; Ani Mardiastuti; Yeni A. Mulyani (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Green space which is available in Jakarta could be used as a birds habitat. The study of the feeding guild may be a useful indicator of the environment disturbance. Therefore, this study was expected to provide information on the bird composition by using the feeding guild as consideration in managing green space in Jakarta. Bird species data obtained from research during May to July 2014 were grouped based on the response to the feeding guild. Bird species were grouped into 12 feeding guilds and every species could only had one feeding guild. Based on studies in 21 green space in Jakarta, 162 species of birds were found with the insectivorous birds in tree canopy (36 species or 22,22%) and fish eater (28 species; 17,28%) as the most dominant feeding guild.Keywords: bird, DKI Jakarta, feed, green space, guild